Joint power contribution during jumping and sidecutting in young female elite handball players - Bencke, J.; Lauridsen, H. B.; Sørensen, R. S.; Aagaard, P.; Zebis, M. K. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: One game-changing parameter in handball is explosive power during jumping or sidecutting. In order to improve game performance, more knowledge about the physical demands of the different joints and muscle groups during sports specific movements may help trainers to implement specific exercises for enhancing performance in these movements. The aim of this study was to describe the kinematics and kinetics of the ankle, knee and hip joint during jumping and sidecutting, and investigate their relation to optimal performance. Methods: 54 young female handball players (16.8 yrs, SD: 1.3) were recruited from Danish national youth teams. Threedimensional movement analysis was used to investigate maximal counter movement jumping (CMJ) and individual sidecutting maneuvers. Maximal flexion ROM of the knee and hip joint was obtained, and eccentric and concentric joint power of the ankle, knee and hip joints were assessed to describe the performance demands imposed on the different joints. In sidecutting, optimal movement performance may be characterized by a high sagittal approach velocity that is translated into a high transverse velocity during a short ground contact. Thus, sidecutting performance was evaluated by the sum of sagittal approach velocity and transverse take-off velocity, divided by ground contact time. For CMJ, jump height was chosen as dependent parameter. Backwards multiple regression analyses were then used to investigate joint power production as primary determinant of CMJ height, and velocity change during sidecutting, respectively. Results: During CMJ maximal knee and hip flexion reached 92 (12) and 97 degrees (9), respectively (0o deg=full extension). During sidecutting, maximal flexion angles were 55 (6) and 52 degrees (11) for the knee and hip joints, respectively. Multiple regression analyses showed that concentric knee joint power was the only determinant of CMJ height (adjusted R2: 0.44, â=0.67, p<0.001). Sidecutting performance was determined by concentric ankle joint power only (adjusted R2: 0.21, â=0.47, p=0.001). Conclusions: Different muscle groups appea ed to be determinants of movement performance in different handball specific movements. While vertical jumping mainly depended on knee joint power, peak concentric ankle joint power was the main determinant of sidecutting performance. Consequently, specific power training of the plantar flexors should be employed to improve sidecutting in handball, while power training of the knee extensors would expect to improve vertical jump performance.